Financial Ratio Analysis of Zakat Management Organization Performance: Evidence from BAZNAS East Jakarta 2021 - Dilla Sepriani; Liza Aulia Putri Sandea; Rianti Rahma; Yunika Kasmita Sari; Ersi Sisdianto (Penerbit Goodwood, 2024)
Purpose: Badan Amil Zakat Nasional (BAZNAS) is Indonesia’s national statutory zakat institution responsible for managing Zakat, Infaq, and Sedekah (ZIS) funds for mustahik, including microenterprise operators and economically vulnerable groups. This study analyzes the financial performance of BAZNAS East Jakarta for 2021–2022 using the official ratio framework issued by Puskas BAZNAS.Methodology: A descriptive quantitative approach was applied using audited financial statements for the year ending 31 December 2022. The analysis employs three Puskas BAZNAS ratio indicators, namely the fundraising cost ratio, the amil fund ratio covering zakat and infaq/sedekah allocations, and the operational cost growth ratio, calculated and interpreted based on standardized benchmarks.Results: The fundraising cost ratio indicates inefficiency in both years (2021: 111%, 2022: 102%). The amil fund ratios remain in the good category and show improvement, while the operational cost growth ratio is stable and proportional to ZIS collection growth.Conclusions: BAZNAS East Jakarta demonstrates strong governance in amil fund allocation and operational efficiency, although fundraising efficiency requires improvement to maximize distributable funds.Limitations: The study is limited to two years of data from a single regional office.Contributions: The study applies the Puskas BAZNAS ratio framework empirically and provides a replicable performance evaluation model for zakat institutions.